2015
DOI: 10.15405/ejsbs.159
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Coaching - A Strategy for Promoting Behavioural Self-Regulation in Children/Young People In Schools: A Pilot Study

Abstract: Emotion coaching is a parenting style clinically observed in the USA which supports children's emotional self-regulation, social skills, physical health and academic success. A pilot study in a rural disadvantaged area in England sought to evaluate the effectiveness of training practitioners who work with children and young people in schools, early years settings and youth centres to apply emotion coaching strategies in professional contexts, particularly during emotionally intensive and behavioural incidents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
7
20
0
Order By: Relevance
“…Moreover, there lacks a study that investigated how concurrent EC implementation -at home and at school -is supportive for children. Rose et al are consistent with those found in parental clinical settings [34]: Adult's meta-emotion philosophy changed as a result of Emotion Coaching training, which enabled increased adult self-regulation. Disruptive behavior decreased and pro-social behavior increased in children and young people.…”
Section: Emotion Coachingsupporting
confidence: 77%
See 3 more Smart Citations
“…Moreover, there lacks a study that investigated how concurrent EC implementation -at home and at school -is supportive for children. Rose et al are consistent with those found in parental clinical settings [34]: Adult's meta-emotion philosophy changed as a result of Emotion Coaching training, which enabled increased adult self-regulation. Disruptive behavior decreased and pro-social behavior increased in children and young people.…”
Section: Emotion Coachingsupporting
confidence: 77%
“…Gus, Rose and Gilbert [33] proposed Emotion Coaching as a universal, simple, low-cost strategy for educational settings. Emotion Coaching enhances adult's communication skills in relating effectively with children and young people about emotions and behavior [34]. It is an approach to support the development of emotional regulation in children through attuned relationships.…”
Section: Emotion Coachingmentioning
confidence: 99%
See 2 more Smart Citations
“…The implications of the study relate to victim-focused anti-bullying intervention programmes. For example, emotion coaching has been used in schools to help children self-regulate their own emotions (Katz et al, 2012), with recent UK-based research suggesting that this intervention programme promotes the development of emotional competencies and enhances relationships (Rose, McGuire-Snieckus, & Gilbert, 2015). The findings from the current study emphasise the importance of emotion coaching for children, in particular the development of skills that promote cognitive reappraisal of emotions.…”
Section: Discussionmentioning
confidence: 65%